2008
DOI: 10.1038/ng.85
|View full text |Cite
|
Sign up to set email alerts
|

A phenylalanine in DGAT is a key determinant of oil content and composition in maize

Abstract: Plant oil is an important renewable resource for biodiesel production and for dietary consumption by humans and livestock. Through genetic mapping of the oil trait in plants, studies have reported multiple quantitative trait loci (QTLs) with small effects, but the molecular basis of oil QTLs remains largely unknown. Here we show that a high-oil QTL (qHO6) affecting maize seed oil and oleic-acid contents encodes an acyl-CoA:diacylglycerol acyltransferase (DGAT1-2), which catalyzes the final step of oil synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
288
0
11

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 389 publications
(312 citation statements)
references
References 20 publications
13
288
0
11
Order By: Relevance
“…Arabidopsis is only a model species and has not been subjected to artificial selection for agronomic traits such as seed oil content or yield. However, WRI1 and DGAT1 overexpression have been reported individually to boost seed oil content in maize (Zheng et al, 2008;Shen et al, 2010) and oilseed rape (Brassica napus; Weselake et al, 2008;Wu et al, 2014). Furthermore, suppression of SDP1 can also enhance seed oil content in oilseed rape (Kelly et al, 2013a) and Jatropha curcas (Kim et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Arabidopsis is only a model species and has not been subjected to artificial selection for agronomic traits such as seed oil content or yield. However, WRI1 and DGAT1 overexpression have been reported individually to boost seed oil content in maize (Zheng et al, 2008;Shen et al, 2010) and oilseed rape (Brassica napus; Weselake et al, 2008;Wu et al, 2014). Furthermore, suppression of SDP1 can also enhance seed oil content in oilseed rape (Kelly et al, 2013a) and Jatropha curcas (Kim et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Until recently, however, this had not been demonstrated in a major crop. Zheng et al (2008) reported that expression in maize of an ancestral maize DGAT1 allele, PH09B, under control of the oleosin promoter resulted in an increase in kernel oil of about 1% (by weight). We have also observed that increasing DGAT activity in maize, by expression of UrDGAT2A in the germ, elevated kernel oil content (D. Hawkins, D.L.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies conducted under greenhouse conditions, in Arabidopsis (Arabidopsis thaliana) and maize (Zea mays), have demonstrated that increasing DGAT activity during seed development can impact the final oil content in seed (Jako et al, 2001;Zheng et al, 2008). In these studies, endogenous DGAT1 genes were overexpressed in their native hosts and achieved absolute increases in oil of 9% to 12% for Arabidopsis and approximately 1% for maize.…”
mentioning
confidence: 99%
“…In Arabidopsis, AtDGAT1 controls TAG biosynthesis in developing seeds, whereas AtDGAT2 seems to have no obvious phenotype functionally (Shockey et al 2006;Zhang et al 2009). Similarly, the DGAT1s significantly regulate TAG accumulation in maize (Zheng et al 2008), Tropaeolum majus L. (Xu et al 2008) and soybean (Li et al 2010b). Further, studies have shown that the DGAT2s play a critical role in the accumulation of unusual FAs (such as epoxy and hydroxy fatty acids) in castor bean (Kroon et al 2006), tung tree (Shockey et al 2006) and Vernonia (Li et al 2010a).…”
Section: Introductionmentioning
confidence: 99%